Public knowledge of self-medication in Ngaglik subdistrict of Sleman regency - Dian Medisa; Fithria Dyah Ayu Suryanegara; Ditya Ayu Natalia; Puspita Fitri Handayani; Dhea Putri Indra Kusuma; Diesty Anita Nugraheni (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2020)
Background: Self-medication is using medicines without a prescription or health professional advice. Over-the-counter (OTC) medicines are commonly used in self-medication. Knowledge and practices of self-medication is required to be assessed to ensure appropriate uses of medicines.Objective: This study is to examine public knowledge and practices of self-medication in Subdistrict of Ngaglik, Sleman, D.I. Yogyakarta.Methods: A cross-sectional survey was conducted in three villages in Ngaglik, Sleman. 339 participants were selected through a cluster sampling. Data were collected by using a self-administered questionnaire. Descriptive analysis and chi-square test were used to analyse the data.Results: Most of participants were female (61.7%) aged between 26-45 years (49.9%). More than fifty percent of participants (59%) had education level of senior high school, and 49.9% participants had good knowledge of the OTC self-medication. The level of knowledge of self-medication was significantly associated with the level of education (p values<0.05). The most commonly used OTC medicines for self-medication were analgesics and antipyretics (48.4%), respiratory drugs (29.7%), and gastrointestinal drugs (9.6%). OTC medicine advertisements were common sources of information about medicines for self-medication (39.5%) whereas information sources from health professionals were accounted for only 2.4%.Conclusion: The public knowledge of self-medication needs to be developed. Health professionals, especially pharmacists, are suggested to provide more information on the OTC medicines for public to allow them to access additional information sources than medicine advertisements.